Resilience Programs for Children and Adolescents: A Systematic Review and Meta-Analysis - Pinto, Tatiana Matheus; Laurence, Paulo Guirro; Macedo, Cristiane Rufino; Macedo, Elizeu Coutinho (Frontiers in Psychology, 2021)
Resilience may be defined as the ability to recover and adapt to adverse situations. Given that resilience involves cognitive and behavioral aspects, it could be promoted based on strategies that favor them, especially during childhood and adolescence. As a result, several resilience-focused programs have been developed and studied. This systematic review of Randomized Clinical Trials (RCTs) aimed to assess resilience-focused programs for children (<12 years old) and adolescents (12 to 22 years old) compared to active (treatment as usual, other program modalities, educational curriculum at school) or inactive (waiting list, no treatment) control groups. We performed a systematic review of meta-analyses of randomized clinical trials (RCTs). The following databases were searched: Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, Embase, and PsycINFO. Two authors independently selected the studies, extracted the data, and assessed the studies’ risk of bias. Meta-analyses of random effects were conducted to calculate the standard mean differences (SMD) and 95% confidence interval (CI) of program effectiveness. Of the 17 RCTs that met the inclusion criteria, 13 provided sufficient data to assess the effectiveness of the programs after their implementation. Meta-analyses indicated overall effectiveness of the programs in promoting resilience (SMD = 0.48, 95% CI [0.15, 0.81], p = 0.0077). The subgroup analysis indicated effectiveness only among adolescents’ resilience (SMD = 0.48, 95% CI [0.08, 0.88], p = 0.02). The follow-up analysis also indicated evidence of continuation of results within a period of up to 6 months up (SMD = 0.12, 95% CI [-0.44, 0.69], p = 0.02). These results indicated the effectiveness of promoting resilience, especially in adolescents, and its continuation in follow-up analyses. These findings are promising in the field of resilience programs; however, further studies are necessary to analyze the different possible characteristics of programs and their results.